Programy przedakcesyjne jako instrument wyrównywania różnic międzyregionalnych w Polsce - Studnicki, Tadeusz; Lemańska-Majdzik, Anna (Pre-Accession Programmes - the Instrument of Balance for Interregional Differences in Poland, 2005)
The paper analyse the effects that the pre-accession funds exert on balancing differences in economic development of Poland. The first part of the paper introduces the general characteristics of the support programmes Poland follows. However, the programmes do not discuss the problem of the region in great detail. The Phare programme has the longest tradition. The remaining two programmes - ISPA and SAPARD were implanted not until 2000. As far as analysed programmes are concerned Phare and SAPARD have greater value for balancing differences, while ISPA promotes further polarization of Polish space. The general influence of the programmes is rather ambiguous. Both less and better developed regions undertake the programmes. From the geographical point of view, regions located along the western and southern border of Poland, as for example Małopolska Region, considerably benefit from the programmes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 227-240